Bile Acids Activated Receptors Regulate Innate Immunity - Fiorucci, Stefano; Biagioli, Michele; Zampella, Angela; Distrutti, Eleonora (Frontiers in Immunology, 2018)
Once known exclusively for their role in nutrients absorption, primary bile acids, chenodeoxycholic and cholic acid, and secondary bile acids, deoxycholic and lithocholic acid, are signaling molecules, generated from cholesterol breakdown by the interaction of the host and intestinal microbiota, acting on several receptors including the G Protein-Coupled Bile Acid Receptor 1 (GPBAR1 or TGR5) and the Farnesoid-X-Receptor (FXR). Both receptors are placed at the interface of the host immune system with the intestinal microbiota and are highly represented in cells of innate immunity such as intestinal and liver macrophages, dendritic cells and natural killer (NK) T cells. Here, we review how GPBAR1 and FXR modulate the intestinal and liver innate immune system and contribute to the maintenance of a tolerogenic phenotype in entero-hepatic tissues, and how regulation of innate immunity might help to explain beneficial effects exerted by GPBAR1 and FXR ligands in immune and metabolic disorders.